Doubts about Deconstruction as a General Theory of Translation - Pym, Anthony (TradTerm, 1995)
Comparison of four versions of a sentence from Derrida poses the question of how deconstructionist philosophy should be related to translation theory. Doubts are raised with respect to the general pertinence of deconstruction, the possibility of extending its insight beyond source-text analysis, and the reasons for a certain residual inferiorization of translation. It is suggested, in the spirit of quiet dissent, that translation theory should not be unduly upset by the fact that source texts are semantically unstable points of departure.